IDENTIFIKASI DAN PENETAPAN KADAR SENYAWA TANIN PADA EKSTRAK DAUN BIDURI (Calotropis gigantea) METODE SPEKTROFOTOMETRI UV-VIS - Yuska Noviyanty; Hepiyansori Hepiyansori; Yudan Agustian (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2020)
Calotropis gigantea (Biduri) are plants that are widely used as herbal medicines by the community. Calotropis gigantea (Biduri) is used as a medicine for coughing, hives, medication for toothache, medicine for ear pain, epilepsy, wounds, sprains and diarrhea. The chemical content of Calotropis gigantea (Biduri) is in the form of glycosides, saponins, alkaloids, flavonoids, and tannins. The purpose of this study was to determine the presence or absence of tannin compounds and levels of tannin compounds in Calotropis gigantea (Biduri). The identification test used FeCl3 and gelatin reagent. Extraction was carried out by maceration using ethanol 96% solvent. Determination of tannin levels of. Calotropis gigantea (Biduri) by Uv-vis spectrophotometry method. The results of the identification test showed that Calotropis gigantea (Biduri) positively contained tannins with FeCl3 resulting in a blackish green color and gelatin causing deposits. The results of the average level of tannins in biduri leaf extract Calotropis gigantea (Biduri) at a concentration of 100 ppm of 1.16 µg / ml, a concentration of 200 ppm of 3.53 μg / ml and a concentration of 300 ppm of 7.12 μg / ml.